2005
DOI: 10.1080/01650250544000053
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mental state understanding in preschoolers of varying socioeconomic backgrounds

Abstract: Two studies investigated the influence of age, language, and family background on the development of preschoolers' social cognitive skills. Study 1 examined variability in economically disadvantaged preschoolers' understanding of fantasy and evaluated the relation of age and language to children's skill in this area. Children were shown drawings of fantasy and real-life events and asked if the event could happen in real life and to justify their responses. Children were more likely to answer correctly when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Others have found aspects of preschoolers' social cognition to be related to SES (e.g. Garner et al, 2005). Because part of this effect may be due to the lower language ability of children at socioeconomic risk (Nelson et al, 2011), it is important to replicate this finding with the addition of a measure of language ability.…”
Section: Differences According To Child Characteristicsmentioning
confidence: 96%
“…Others have found aspects of preschoolers' social cognition to be related to SES (e.g. Garner et al, 2005). Because part of this effect may be due to the lower language ability of children at socioeconomic risk (Nelson et al, 2011), it is important to replicate this finding with the addition of a measure of language ability.…”
Section: Differences According To Child Characteristicsmentioning
confidence: 96%
“…A final possibility is simply that improving theory of mind understanding does not improve social competence. Although several researchers have shown that theory of mind and social competence are related (e.g., Denham et al, 2012; Weimer & Guajardo, 2005), other researchers have found that false belief understanding did not relate to social competence (e.g., Garner, Curenton, & Taylor, 2005), or that false belief understanding correlated with only certain aspects of social competence (e.g., Lalonde & Chandler, 1995). Thus, improving theory of mind may not be a viable means for improving social competence.…”
Section: Discussionmentioning
confidence: 97%
“…This could be attributed to a range of methodological issues but also raises the possibility of important within-culture variations in naïve psychology. Some studies have provided evidence that within culture, the rates of development will vary according to number of siblings (e.g., Perner et al, 1994;Jenkins and Astington, 1996); birth order (e.g., Ruffman et al, 1998;Howe et al, 2005); availability of extended family members (e.g., Lewis et al, 1996); socioeconomic status (e.g., Holmes et al, 1996;Cutting and Dunn, 1999;Garner et al, 2005), parenting style (e.g., Ruffman et al, 1999Ruffman et al, , 2006Vinden, 2001); language development (e.g., Astington, 2001;Astington and Baird, 2005); within-family communication about mental states (e.g., Dunn and Dale, 1984;Dunn et al, 1987Dunn et al, , 1991Youngblade and Dunn, 1995;Ruffman et al, 2002); genetic influences (e.g., Hughes and Cutting, 1999); and family relationships (e.g., Hughes et al, 2005). These subtle differences are also likely to be evident between cultures and while gross cultural differences are important more subtle cultural variations, particularly where cultures are distinct but similar, should not be ignored.…”
Section: Cultural Universals and Differences In Naïve Psychologymentioning
confidence: 99%